Partial Recovery of Alcohol Dependence-Related Deficits in Sleep Evoked Potentials Following 12 Months of Abstinence - Colrain, Ian M.; Padilla, Mayra L.; Baker, Fiona C. (Frontiers in Neurology, 2012)
Stimuli presented during sleep can produce an evoked EEG delta wave referred to as a K-complex. These responses occur when large numbers of cortical cells burst fire in a synchronized manner. Large amplitude synchronized scalp responses require that the CNS contain large numbers of healthy neurons that are interconnected with highly functional white matter pathways. The P2, N550, and P900 components of the evoked K-complex are sensitive measures of normal healthy brain aging, showing a decrease in amplitude with age. N550 and P900 amplitudes are also reduced in recently detoxified alcoholics, most dramatically over frontal scalp regions. The present study tested the hypothesis that the amplitude of K-complex related evoked potential components would increase with prolonged abstinence. Fifteen alcoholics (12 men) were studied twice, separated by a 12 month period, during which time they were followed with monthly phone calls. Subjects were aged between 38 and 60 years at their first study. They had on average a 29.3 ± 6.7 year drinking history and had been abstinent for between 54 and 405 days at initial testing. Evoked K-complexes were identified in the EEG and averaged to enable measurement of the P2, N550 and P900 peaks. Data were collected from seven scalp sites (FP1, FP2, Fz, FCz, Cz, CPz, and Pz). N550 and P900 amplitudes were significantly higher after 12 months of abstinence and an improvement of at least 5 μV occurred in 12 of the 15 subjects. N550 and P900 also showed highly significant site by night interactions with the largest increases occurring over prefrontal and frontal sites. The data indicate that the sleep evoked response may provide a sensitive marker of brain recovery with abstinence from alcohol.